The pharmacological and hormonal therapy of hot flushes in breast cancer survivors - Wiśniewska, Iwona (Breast Cancer, 2015)
The side effects of oncological treatment, which appear during or after therapy, are sometimes very annoying for patients and are not adequately treated by physicians. Among the symptoms experienced by breast cancer patients are hot flushes, which result from a natural or cancer therapy-induced menopause. The intensity of hot flushes in breast cancer patients may be more severe than those experienced by women undergoing a natural menopause. Taking into account the incidence of breast cancer and long-lasting hormone-suppression therapies, the problem of hot flushes will affect many women. Hormonal replacement therapy, the most effective therapeutic means for alleviating hot flushes, is usually contraindicated for breast cancer patients. For intense and severe hot flushes, pharmacological treatment using agents from a group of selective serotonin reuptake inhibitors and serotonin and norepinephrine reuptake inhibitors such as venlafaxine or citalopram may be introduced. Other agents from different pharmacological groups, such as clonidine, gabapentin, or pregabalin, have also proved to be effective in treating hot flushes. The efficacy of phytoestrogens has not been proven in randomized clinical trials. The importance of the placebo effect in decreasing vasomotor symptoms has also been reported in many research papers. Educating breast cancer patients in lifestyle changes which decrease the frequency and intensity of vasomotor symptoms can offer significant help too. This paper reviews the current state of research in order to assess the options for the treatment of hot flushes in breast cancer survivors.